2017
DOI: 10.1111/petr.13000
|View full text |Cite
|
Sign up to set email alerts
|

Successful liver transplantation for non‐resectable desmoplastic nested spindle cell tumor complicated by Cushing's syndrome

Abstract: Desmoplastic spindle cell tumors of liver are rare tumors of low malignant potential characterized by well-demarcated nests of spindle and epithelioid cells in a dense desmoplastic stroma. While surgery remains the definitive treatment, there have been reports of tumor recurrence locally and metastasis which respond poorly to chemotherapy. Hepatic transplant has been attempted in cases of recurrence or large size of primary tumor. Long-term follow-up and imaging surveillance are required as these tumors have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…Calcifying Nested Stromal Epithelial Tumor (CNSET) is an exceptionally uncommon primary hepatic tumor that occurs in children and young adults, with only about 40 cases reported in the literature [36]. While localized disease is often effectively cured with surgical resection, recurrent and de novo metastatic disease demonstrates chemotherapy resistance and there are no proven therapeutic options [37][38][39][40].…”
Section: Pharmacotypes Identification For Clinical Trial Designmentioning
confidence: 99%
“…Calcifying Nested Stromal Epithelial Tumor (CNSET) is an exceptionally uncommon primary hepatic tumor that occurs in children and young adults, with only about 40 cases reported in the literature [36]. While localized disease is often effectively cured with surgical resection, recurrent and de novo metastatic disease demonstrates chemotherapy resistance and there are no proven therapeutic options [37][38][39][40].…”
Section: Pharmacotypes Identification For Clinical Trial Designmentioning
confidence: 99%
“…Treatment considerations for CNSET include wedge resections for smaller tumors and more substantial interventions in the form of partial hepatectomy or liver transplant for larger tumors. 22,28,29 Chemotherapy using soft tissue sarcoma or hepatoblastoma protocol has been reported in the literature. However, it is unclear whether chemotherapy has any significant role in preventing tumor recurrence, as the complete resection of tumor has proved curative in more than half of the reported cases.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…However, it is unclear whether chemotherapy has any significant role in preventing tumor recurrence, as the complete resection of tumor has proved curative in more than half of the reported cases. 29 Furthermore, preoperative chemotherapy has not shown effect on shrinkage or necrosis of the tumors in subsequent resections or imaging studies. 2,4,6,19,20,22,29 Thus, it is still uncertain whether chemotherapy holds any benefit with the current data available.…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…The tumor usually does not manifest early symptoms and is mostly diagnosed incidentally, as a singular mass averaging 12.6 cm in size ( 30 ). Laboratory results lack abnormalities, although some authors ( 2 , 4 , 7 , 11 , 12 , 21 , 25 , 28 ) reported the coexistence of CNSET with Cushing's Syndrome, therefore, elevated levels of adrenocorticotropic hormone (ACTH) may be observed.…”
Section: Introductionmentioning
confidence: 99%